Komposit Hibrid Polyester Berpenguat Serbuk Batang dan Serat Sabut Kelapa - Lumintang, Romels C. A.; Soenoko, Rudy; Wahyudi, Slamet (Jurnal Rekayasa Mesin, 2011)
Sawdust coconut trunks of palm trees and fiber coconut coir are two waste materials from the processing of coconuts and coconut tree trunks sawmill waste are plentiful materials can be utilized for producing composites using polyester resins. Both each properties materials as follow polyester resin: liquid in the open air conditions, sawdust coconut and coconut coir fiber properties is lightweight and fragile nature of the polyester adhesive used as a binder (binder) between fiber coconut coir and sawdust coconut palm tree trunks as a filler. The variation volume fraction between the sawdust and coconut trunks of fiber coconut coir in polyester resin influence mechanical properties for each composition of this composite. By comparizing the volume fraction of either polyester, sawdust coconut palm tree trunks and fiber coconut coir (Coir coconut) using tensile test standard ASTM D638-I, and the ASTM D6110 for impact testing. The result of tensile and impact test, obtained that the optimum percentage 30:10 per cent, mean tensile strength on 95.953 N/mm2 , mean elasticity 0,125 % , mean elasticity modulus 768.702 N/mm2, mean absorbed energy 2,679 J and mean impact value 0,068 J/mm2. Keywords: Polyester, Sawdust coconut, coconut coir fiber, mechanical properties